‘Twisting herself into all shapes’: blackface minstrelsy and comic performance in Harriet Wilson’s Our Nig - Elizabeth Boyle (European Journal of American Studies)
This article argues that the practical jokes running throughout Wilson’s novel Our Nig; or Sketches from the Life of a Free Black (1859) are evidence of a deliberate and sophisticated comic strategy that exploits the spectacular body’s potential for subversive performance and works against the alienating conditions of social and political marginalisation experienced by African Americans in the antebellum period. Initially utilising the crude humour of minstrelsy, Wilson deliberately capitalised on her readers’ laughter in order to defamiliarise the ‘spectacle’ of blackness in both popular performance culture and indentured servitude. Using movement, costume and material props, Wilson imagines new ways to present her protagonist’s body through the minstrel stereotypes of Topsy, Jim Crow, Zip Coon and Jasper Jack. Wilson then turns the joke on her white readers, ultimately demonstrating that whiteness, like blackness, is a performative identity. Taken as a whole, Wilson’s comic strategy, with its ‘embodied insurgency’, aligns her with the period’s most politically racial African American performers.